Factors Associated with High Live Release for Dogs at a Large, Open-Admission, Municipal Shelter - Patronek, Gary J. (Animals (Basel), 2018)
SIMPLE SUMMARY: Better understanding of factors contributing to live release (rehoming) may help shelters improve outcomes. In this study, data were analyzed for all dogs (n = 21,409) admitted over a two-year period for the primary purpose of rehoming at a high-volume, open-intake municipal shelter performing animal control (the Pima Animal Care Center in Tucson, Arizona). Results show that >88% of eligible dogs were rehomed through adoption to the public or transfer to a rescue group. Temporary placement into interim foster homes of dogs who were either not immediately eligible or not strong candidates for adoption due to reasons such as age or health, increased the odds of live release after subsequent return to the shelter, especially for adult dogs. Dogs returned to the shelter after unsuccessful adoption had a live-release advantage as well, which suggested that the temporary experience in a home was not detrimental and may have facilitated the likelihood of live release after return, akin to a foster situation. Over a fifth (21.1%) of dogs originally brought to the shelter for owner-requested euthanasia were determined to be potentially savable and ultimately rehomed. It remains to be determined whether other large, open intake shelters performing animal control can replicate these results. ABSTRACT: Better understanding of factors contributing to live release (rehoming) may help shelters improve outcomes. In this cross-sectional, exploratory, non-interventional study, data for all intakes (n = 21,409) for dogs eligible for rehoming from 1 January 2015 to 31 December 2016 are analyzed to identify such factors. Live release was >88%. A total of 1510 (7.1%) dogs interacted with the foster care system, 98.9% of whom had live release. Foster care increased the odds of live release by about five-fold for all dogs (odds ratio (OR) 5.30 (95% confidence interval (CI): 3.13; 8.97), p < 0.001) and by >20-fold for adult dogs (OR 22.2 (95% CI: 5.48; 90.2), p < 0.001) compared to first-time owner-surrendered dogs. Dogs returned from foster care had a 70% reduction in health concerns, as judged by intake staff, compared with dogs sent to foster. In addition to saving 2882 lives, the rescue network utilized by this shelter was estimated as having reduced in-shelter care needs by 13,409 animal care-days over two years. Dogs returned from adoption also had increased odds of live release (OR 4.74 (95% CI: 3.02; 7.44), p < 0.0001). Nearly a third (29.6%) of dogs originally brought in by owners for euthanasia were determined to be potentially savable, and a fifth of the original group (21.1%) were ultimately placed. Less than 4% of dogs presented with behavioral concerns at intake. It remains to be determined whether other large, open intake shelters performing animal control can replicate these results.